Analisa Bisnis Internasional Pada Perusahaan Wings Group - Edy Yulianto Putra; Wirren Chang; Agnes Doraresta Khatarina Tokan; Dewi; Mardiana Ng; Serina Serina (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
International business ventures require people to communicate and cross cultural and national boundaries. Along with the trend towards a global economy, there is now greater recognition among specialists that cultural differences affect all aspects of international business. The resulting phenomenon means increased business links between markets and individual territories, which as a consequence often brings about the need to confront existing cultural differences. Therefore, it becomes important to include cultural aspects by entities involved in international business and able to overcome challenges caused by cultural differences. The method used in this research is a literature study.